PERSEPSI PEKERJA TERHADAP WORK FROM HOME (WFH) DI MASA PANDEMIK COVID-19 - REGY CITRA PERDANA; YOSART ADI SUYOSO; ANA YULIANA; MUHAMMAD RISQI AGUSTINO; DEDI HARTAWAN (Jurnal Inovasi Bisnis dan Kewirausahaan, 2021)
ABSTRACT This study aims to perceptions of Work From Home (WFH) received by workers who previously worked regularly at the office. This change makes the workers change physically and mentally. The research method used is a qualitative method with interviews with respondents in accordance with the requirements. The technique used is the documentation technique for collecting data from various sources and information. The type of data is secondary data from research results sourced from the media and news.